Comparative analysis of bobbin tool and one-step double-acting tool in friction stir welding of aluminum AA1100 - Yudha Eko Widyantono; Yoshihiko Uematsu; Ilhamdi; Sulardjaka; Jos Istiyanto; Muizuddin Azka; Nurul Muhayat; Triyono (International Journal of Lightweight Materials and Manufacture, 2025)
Aluminum's lightweight nature and corrosion resistance make it a preferred material across various industries, including marine, automotive, railway, and aerospace sectors. However, traditional fusion welding of aluminum often leads to significant defects such as porosity and distortion. Friction Stir Welding (FSW), a solid-state welding technique, addresses many of these challenges but has limitations when welding thick plates, which can be alleviated through the use of a bobbin tool. This study presents a comparative analysis of a novel one-step double-acting tool, which operates dual tools simultaneously on both surfaces of the workpiece, against the bobbin tool. Aluminum AA1100 sheets measuring 200 × 240 mm and 8 mm thick were welded using both methods under standardized parameters: a tool rotation speed of 1500 rpm, a plunge depth of 0.2 mm, a travel speed of 25 mm/min, and a tilt angle of 2°. By varying the offset of the one-step double-acting tool between 0 mm and 2 mm, the impact on bead appearance and mechanical properties was assessed. Results indicated that the bobbin tool produced rougher beads and tear defects due to its design, while the one-step double-acting tool, particularly at a 2 mm offset, yielded cleaner, more uniform welds with fewer defects and enhanced material control. Microstructural analysis showed that the stir zone exhibited uniform grain refinement, and the Heat-Affected Zone (HAZ) benefited from finer grain structures due to improved heat management. Hardness testing revealed a characteristic W-shaped distribution, and tensile strength evaluations demonstrated the superior joint quality of the 2 mm offset, outperforming the bobbin tool in tensile strength and defect reduction. Although the bobbin tool showed slightly higher average strength in bending tests, the one-step double-acting tool proved to be more consistent and reliable.